The spaces of the modern city : imaginaries, politics, and everyday life - Prakash, Gyan, 1952-; Kruse, Kevin M., 1972- (Princeton : Princeton University Press, 2008)
By United Nations estimates, 60 percent of the world's population will be urban by 2030. With the increasing speed of urbanization, especially in the developing world, scholars are now rethinking standard concepts and histories of modern cities. The Spaces of the Modern City historicizes the contemporary discussion of urbanism, highlighting the local and global breadth of the city landscape. This interdisciplinary collection examines how the city develops in the interactions of space and imagination. The essays focus on issues such as street design in Vienna, the motion picture industry in Los Angeles, architecture in Marseilles and Algiers, and the kaleidoscopic paradox of post-apartheid Johannesburg. They explore the nature of spatial politics, examining the disparate worlds of eighteenth-century Baghdad, nineteenth-century Morelia, Cold War-era West Berlin, and postwar Los Angeles. They also show the meaning of everyday spaces to urban life, illuminating issues such as crime in metropolitan London, youth culture in Dakar, "memory projects" in Tokyo, and Bombay cinema. Informed by a range of theoretical writings, this collection offers a fresh and truly global perspective on the nature of the modern city. The contributors are Sheila Crane, Belinda Davis, Mamadou Diouf, Philip J. Ethington, David Frisby, Christina M. Jiménez, Dina Rizk Khoury, Ranjani Mazumdar, Frank Mort, Martin Murray, Jordan Sand, and Sarah Schrank.
Introduction -- Spatial imaginaries -- Streets, imaginaries, and modernity: Vienna is not Berlin / David Frisby -- The global spaces of Los Angeles, 1920s-1930s / Philip J. Ethington -- Architecture at the ends of empire: urban reflections between Algiers and Marseille / Sheila Crane -- The city in fragments: kaleidoscopic Johannesburg after apartheid / Martin J. Murray -- Spatial politics -- Violence and spatial politics between the local and imperial: Baghdad 1778-1810 / Dina Rizk Khoury -- From the lettered city to the sellers' city: vendor politics and public space in urban Mexico, 1880-1926 / Christina M. Jiménez -- The city as theater of protest: West Berlin and West Germany, 1962-83 / Belinda Davis -- Nuestro pueblo: the spatial and cultural politics of Los Angeles' Watts Towers / Sarah Schrank -- Spaces of everyday life -- Morality, majesty, and murder in 1950s London: metropolitan culture and English modernity / Frank Mort -- (Re)Imagining an African city: performing culture, arts, and citizenship in Dakar (Senegal), 1980-2000 / Mamadou Diouf -- Street observation science and the Tokyo economic bubble, 1986-1990 / Jordan Sand -- Spectacle and death in the city of Bombay cinema / Ranjani Mazumdar -- Index.
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Cities and towns -- Case studies; Sociology, Urban -- Case studies; Villes -- Études de cas; Sociologie urbaine -- Études de cas; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; Cities and towns; Sociology, Urban; Urbanització.; Sociologia urbana; Sociologia urbana; Case studies